2016
DOI: 10.1186/s13098-016-0134-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific associations of serum sex hormone-binding globulin with features of metabolic syndrome in children

Abstract: BackgroundSex hormone-binding globulin (SHBG) has been proposed as a biomarker of MetS in children and adults. We aim to determine the associations of SHBG with components of MetS in children from the Middle-East where the prevalence of MetS are on the rise.MethodsIn this cross-sectional study, a total of 509 randomly selected school children (226 boys and 283 girls) aged 12–16 years were recruited. Fasting blood glucose and lipid profile were determined using routine laboratory procedures. Serum SHBG is measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that low SHBG levels are predictive of higher risk for developing hypertension [5], T2D [6], and MetS [7,8]. A cross-sectional study showed that SHBG is a sensitive predictor of MetS in Arab adolescents [9]. There are limited data available about the association between circulating serum SHBG levels and MetS in the Saudi male population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that low SHBG levels are predictive of higher risk for developing hypertension [5], T2D [6], and MetS [7,8]. A cross-sectional study showed that SHBG is a sensitive predictor of MetS in Arab adolescents [9]. There are limited data available about the association between circulating serum SHBG levels and MetS in the Saudi male population.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of scientific evidence confirming the role of sex hormones in the development of MetS. An inverse association between serum SHBG levels and the prevalence of MetS has been observed in children aged 12–16 years, with SHBG being a more sensitive marker of MetS in boys, but not in girls, indicating sexual dimorphism already at an early age [ 234 ]. At older ages, an association between lower SHBG levels and MetS is still observed in both males and females, while total and free testosterone levels are lower in males and higher in females with MetS [ 235 237 ].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…found that lower SHBG was more significantly related to developing metabolic diseases than lower TT in community-dwelling men older than 70 years in Perth, Western Australia ( 21 ). And another cross-sectional research found that SHBG was a highly sensitive predictor of MetS in Arab adolescents ( 22 ). However, few studies have examined the relationship between serum SHBG levels and MetS in populations of Chinese men.…”
Section: Introductionmentioning
confidence: 99%